Connectedness Is Critical: A Social Network Analysis to Support Emerging Women Leaders in Global Health - Angelica Lopez Hernandez; Jennifer L. Weinberg; Amena El-Harakeh; Lola Adeyemi; Neelima Potharaj; Nandini Oomman; Anna Kalbarczyk (Ubiquity Press, 2022)
Background: Global health networks serve to bring members together towards a specific objective. However, for myriad reasons, women often lack access to networks that facilitate leadership and career development. In 2020, the Johns Hopkins Center for Global Health launched Emerging Women Leaders in Global Health (EDGE) with a virtual seminar series featuring diverse women leaders followed by an online networking space. Objectives: The purpose of this paper is to use social network analysis (SNA) to describe the network, the connections within it, and the values placed on those connections to inform future programming. Methods: We asked EDGE participants to fill out a survey to collect network-specific data. Then, we developed a sociogram and calculated social network metrics based on region, type of organization, and professional career stage. Findings: The EDGE network had 103 unique connections, and each node, on average, was connected to two other nodes. Early professionals that work in Global North academic institutions were the most prevalent members and most efficiently connected with other members of the network. However, senior professionals from the Global South are key to bridging gaps between regions and across sectors. Conclusions: Early career professionals from the Global North and senior professionals from the Global South need to work in synergy to improve the connectedness of emerging women leaders around the world.